A The Strategies of Sellers in Mobility Market Viewed from Socio-economic Perspective - Rahayu, Sri; Irwan, Irwan; Ariesta, Ariesta (SCAD Independent, 2019)
This research focuses on the strategies of sellers in mobility market viewed from socio-economic perspective. The economic action done by sellers in the market is not only done in one market but also by mobility from one market to another market in Kamang Baru Subdistrict. The action done by sellers in economic activities has happened since 1950s until now and then. So, this phenomenon is very interesting to be researched based on socio- economic perspective to analyze about the strategies of mobility market sellers. The main goal analyzed was the strategies of mobility market sellers when doing economic action in trading activity. Qualitative approach through descriptive method was chosen to analyze the phenomenon. The informants in this research was taken by purposive sampling and the data collecting technique was done by using observation non participant, document, and depth interview. The research result showed that the strategies of sellers in mobility market viewed from socio-economic perspective are the sellers’ rational strategy; the dig holes then close the holes strategy, the sellers’ social capital usage strategy, and the panggaleh or selling culture strategy.